 Proof

Let

A, B

6

=

and

A

B

=

. We need to prove that

A T

(

U

;

τ

)

B

A β

(

Q

(

U

;

τ

))

B

.

Let

A β

(

Q

(

U

;

τ

))

B

. Then

A

B

CC(

Q

(

U

;

τ

)) that is by the theorem 2

we have

A

B

LC(

U

;

τ

). So

x, y

A

B

:

x τ

A

B

y

that is

A T

(

U

;

τ

)

B

.

Let now

A T

(

U

;

τ

)

B

. Then

a

A, b

B

:

τ

(

a, b, A

B

).

Let

X

Y

=

A

B

and

X

Y

=

and

X, Y

6

=

.

By the lemma there exist

a

X

,

b

Y

such that

a

A

,

b

B

(or

a

X

,

b

Y

such that

a

B

,

b

A

what is analogous). So

τ

(

a, b, A

B

) and

consequently

X Q

(

U

;

τ

)

Y

.

Thus

A

B

CC(

Q

(

U

;

τ

)) that is

A β

(

Q

(

U

;

τ

))

B

.

Proposition 17

N

(

β

(

U

;

r

))

N

(

U

;

r

)

for every connector space

(

U

;

r

)

.

Proof

Let

A N

(

β

(

U

;

r

))

B

for some

A, B

6

=

,

A

B

=

, then

A

B

CC(

U

;

r

). Then

A r B

and thus

A N

(

U

;

r

)

B

.

Theorem 17

CC(

β

(

U

;

r

))

CC(

U

;

r

)

for every connector space

(

U

;

r

)

.

Proof

From the previous proposition.

Proposition 18

N

(

β

(

β

(

U

;

r

))) =

N

(

β

(

U

;

r

))

for every connector space

(

U

;

r

)

.

Proof

If

A N

(

β

(

β

(

U

;

r

)))

B

then either

A

B

6

=

and thus

A N

(

β

(

U

;

r

))

B

or

A

B

=

and

A, B

6

=

and

A β

(

β

(

U

;

r

))

B

. Then

A

B

CC(

β

(

U

;

r

))

and thus

A β

(

U

;

r

)

B

with consequence

A N

(

β

(

U

;

r

))

B

.

Let now

A N

(

β

(

U

;

r

))

B

. Then either

A

B

6

=

and thus

A N

(

β

(

β

(

U

;

r

)))

B

or

A

B

=

and

A, B

6

=

and

A β

(

U

;

r

)

B

. So

A

B

CC(

U

;

r

).

X, Y

P

(

A

B

)

\{∅}

: (

X

Y

=

A

B

X

Y

=

∅ ⇒

X

Y

CC(

U

;

r

));

X, Y

P

(

A

B

)

\ {∅}

: (

X

Y

=

A

B

X

Y

=

∅ ⇒

X β

(

U

;

r

)

Y

).

So

A

B

CC(

β

(

U

;

r

)) that is

A β

(

β

(

U

;

r

))

B

and thus

A N

(

β

(

β

(

U

;

r

)))

B

.

Remark 7

CC(

β

(

U

;

r

)) = CC(

U

;

r

) if (

U

;

r

) =

T

(

U

;

τ

) or (

U

;

r

) =

Q

(

U

;

τ

) for

every equivalence link space (

U

;

τ

).

Question 1

β

(

β

(

U

;

r

)) =

β

(

U

;

r

)

?

Question 2

Under which conditions

CC(

β

(

U

;

r

)) = CC(

U

;

r

)

in general?

6. Future research

How connectedness is related with continuity?
Research the lattice of connectors and the lattice of links.
To define product of two connectors is not trivial if possible at all.
We also may attempt to define quotient spaces for connectors.
In my further research I am going to study generalized connectedness of

filters.

20